Pemodelan Kebutuhan Listrik Indonesia Terkait Pencapaian Sasaran Kebijakan Energi Nasional - Sartika; Aryo Prawoto Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Electricity is one of primary demand that is very important to human life, where almost all of human activities rely on electricity. But, as electricity has limited resource, its utilization must be optimized. It is necessary to increase the energy efficiency so that the energy elasticity will be decreasing. Based on one-directional causality from economic development to electricity consumption, it is shown that the application of conservation policy in reducing electricity consumption has no impact to GDP, which is one parameter of economic development. Besides that, the directional causality also suggests that GDP can be used as a variable in building electricity demand model.The national electricity demand modelling is influenced by several variables, including GDP, electricity prices, installed capacity, and total of previous year electricity consumption. Based on RUPTL (General Plan of Power Generation), the additional installed capacity in 2025 is planned to reach 129 GW (Giga Watts). So, the 115 GW installed capacity that already planned by KEN (Kebijakan Energi Nasional – National Energy Policy) could be achieved if the plan could be realized. KEN is also targeting that the amount of total electricity consumption per capita in 2025 reaching up to 2,500 KWh.The demand of electricity until 2025 is estimated using 2 scenarios. The first scenario is based on GDP’s growth as stated in RPJMN for four consecutive year from 2015-2018, i.e. 5.8%, 6.6%, 7.1% and 7.5%. For the period of 2019-2025, an 8% of GDP’s growth is used. Then, second scenario is done by using GDP‘s growth around 9% per year. Based on first scenario, the demand of electricity per capita in 2025 is 2,067.55 KWh, while for second scenario is 2,526.73 KWh. Finally, although the target of installed capacity had been reached, the electricity demand must be supported by a high GDP’s growth. So that, the goals which already targeted by KEN could be achieved. In order to produce appropriate electricity demand, 156 million tonnes coal is needed for first scenario and 196 million tonnes for second scenario.